2001
DOI: 10.1289/ehp.01109s4619
|View full text |Cite
|
Sign up to set email alerts
|

Air pollutant-enhanced respiratory disease in experimental animals.

Abstract: Studies in animals have shown that a wide range of airborne particulates including cigarette smoke, acid aerosols, metals, organic compounds, and combustion products can interfere with the normal defense processes of the lung to enhance susceptibility to respiratory infection or exacerbate allergic diseases. Such detrimental effects are less easy to quantify in humans because of the difficulties in obtaining comprehensive exposure history and health status in large populations and because of the inherent dange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In many cases, these effects have been associated with concomitant increases in susceptibility to respiratory infection (reviewed in [ 6 ]). Numerous experimental studies have demonstrated a decrease in a broad range of innate and adaptive host defenses following inhalation exposure to both single agents or complex mixtures such as cigarette smoke and car exhaust [ 48 ]. While most reports were designed to assess how pollutant exposure affected a subsequent pathogenic challenge, the present study followed the course of viral proliferation during an ongoing exposure to diluted diesel exhaust.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, these effects have been associated with concomitant increases in susceptibility to respiratory infection (reviewed in [ 6 ]). Numerous experimental studies have demonstrated a decrease in a broad range of innate and adaptive host defenses following inhalation exposure to both single agents or complex mixtures such as cigarette smoke and car exhaust [ 48 ]. While most reports were designed to assess how pollutant exposure affected a subsequent pathogenic challenge, the present study followed the course of viral proliferation during an ongoing exposure to diluted diesel exhaust.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning physical health, exposure to air pollution indisputably causes respiratory diseases [14]. Gilmour et al [15] find that human immune function will be weakened if exposed to airborne particulates. de Oliveira Alves et al [16] reveal that exposure to air pollution will strongly increase the levels of inflammatory cytokines and DNA damage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The present knowledge on the effects of air pollution on biodiversity is largely confined to studies conducted in laboratories or focused on individual cases related to the toxicity of pollution exposure(Newman, 1979;Llacuna et al, 1993;Gilmour et al, 2001;Salmón et al, 2018).…”
mentioning
confidence: 99%